The Effect of Concept Attainment Model and Mathematical Logic Intelligence on Introductory Chemistry Learning Outcomes - Aceng Haetami; Maysara Maysara; Eka Cahyana Mandasari (Universitas Pendidikan Ganesha, 2020)
The purpose of this study was to determine the effect of concept attainment model and mathematical logic intelligence on the learning outcomes of introductory chemistry. This research was conducted using a quasi-experimental method with a 2x2 treatment by level design. Total samples are 56 students selected by random sampling. Data analysis used ANOVA with a significance of 0.05. The results showed that: (1) The introductory chemistry learning outcomes of students taught with the concept achievement learning model are higher than those acquainted with the direct learning model; (2) There is the effect of the interaction between learning models and mathematical logic intelligence to study introductory chemistry learning outcomes; (3) The student of learning outcomes taught with the concept attainment model are higher than those taught with the direct learning model for groups of students high logical-mathematical intelligence; (4) The student of learning outcomes taught with the concept attainment model are lower than those taught with the direct learning model for groups of students low logical-mathematical intelligence. Therefore, the use of the learning model should care to aspects of intelligence of learners, so that the learning objectives are expected to be achieved.